2016
DOI: 10.18632/oncotarget.13850
|View full text |Cite
|
Sign up to set email alerts
|

mir-218-2 promotes glioblastomas growth, invasion and drug resistance by targeting CDC27

Abstract: Glioma has become a significant global health problem with substantial morbidity and mortality, underscoring the importance of elucidating its underlying molecular mechanisms. Recent studies have identified mir-218 as an anti-oncogene; however, the specific functions of mir-218-1 and mir-218-2 remain unknown, especially the latter. The objective of this study was to further investigate the role of mir-218-2 in glioma. Our results indicated that mir-218-2 is highly overexpressed in glioma. Furthermore, we showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…Qiu L et al reported that CDC27 induces metastasis and invasion in colorectal cancer via the promotion of epithelial-to-mesenchymal transition [15]. Feng Z et al also demonstrated that Cdc27 is a target for glioblastomas growth, invasion and drug resistance [16]. Our findings showed that the expression levels of E-cadherin were dramatically increased and that the expression levels of Snail and Twist were correspondingly significantly decreased in the shCDC27 cells.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Qiu L et al reported that CDC27 induces metastasis and invasion in colorectal cancer via the promotion of epithelial-to-mesenchymal transition [15]. Feng Z et al also demonstrated that Cdc27 is a target for glioblastomas growth, invasion and drug resistance [16]. Our findings showed that the expression levels of E-cadherin were dramatically increased and that the expression levels of Snail and Twist were correspondingly significantly decreased in the shCDC27 cells.…”
Section: Discussionsupporting
confidence: 61%
“…Besides, increasing reports revealed that CDC27 expression was deregulated in varies of cancers, including breast cancer, and colorectal cancer [13][14][15]. Feng Z et al reported that mir-218-2 promotes glioblastomas growth, invasion and drug resistance by targeting CDC27, and that CDC27 expression may be a significant indicator [16]. Accumulating evidence indicates CDC27 may be involved in the invasion and metastasis of gastric cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several studies have reported that CDC27 can facilitate cell proliferation, migration and invasion in some types of cancers (23)(24)(25). Nevertheless, few studies indicated the opposite influence of CDC27 on cell functions and patients' survival analysis (26,27). The expression and effect of CDC27 in lymphoma has not been reported or clarified.…”
Section: Discussionmentioning
confidence: 99%
“…However, miR-218–5p has been reported to function as an oncogenic miRNA in glioma [54], suggesting that the pro- and anti-cancer roles of miR-218–5p are tumor-type dependent. In addition, miR-218–5p has been found to be downregulated in PCa, which promoted the development, progression, and castration-resistance of PCa via varying mechanisms [13-16].…”
Section: Discussionmentioning
confidence: 99%